Migration: Tightening borders and threats to food security - de Brauw, Alan; Ambler, Kate (International Food Policy Research Institute, 2018)
Recent changes in the political landscape in the United Kingdom and the United States have put tighter borders and migration restrictions on the agenda. Concerns about unchecked migration have also risen in mainland Europe, as migration by boat to Italy from Libya grew rapidly after civil war broke out in the country in 2014. Meanwhile, protracted violence in Central America, the Middle East, and the Lake Chad basin has led to increasing flows of people out of their homes and farms into internally displaced persons (IDP) camps and refugee camps in neighboring countries. Governments in receiving countries have responded to the increasing voluntary and involuntary movement of people out of developing countries and conflict zones either by raising the rhetoric on border enforcement or reducing the number of voluntary migrants and of refugees they are willing to absorb. Yet overall flows of refugees, or forced migrants, may increase in the future. Models of climate change suggest that environmental displacement will increase pressure for migration from environmentally threatened areas of developing countries. And while accurately predicting migratory responses to either environmental degradation or climate change is difficult, recent work definitively links temperature changes to changing migration patterns across countries.